Colonization characteristics of fungi in Polygonum hydropipe L. and Polygonum lapathifolium L. and its effect on the content of active ingredients - Zhang, Xiaorui; Lv, Hongyang; Tian, Maoying; Dong, Zhaowei; Fu, Qinwen; Sun, Jilin; Huang, Qinwan; Wang, Jin (Frontiers in Plant Science, 2022)
Polygonum hydropiper, is a plant of the Persicaria genus, which is commonly used to treat various diseases, including gastrointestinal disorders, neurological disorders, inflammation, and diarrhea. However, because of different local standards of P. hydropiper, people often confuse it with Polygonum lapathifolium L. and other closely related plants. This poses a serious threat to the safety and efficacy of the clinical use of P. hydropiper. This study aims to determine the six active ingredients of P. hydropiper and P. lapathifolium. Then the endophytic fungi and rhizosphere soil of the two species were sequenced by Illumina Miseq PE300. The results show significant differences between the community composition of the leaves, stems, and roots of the P. hydropiper and the P. lapathifolium in the same soil environment. Of the six secondary metabolites detected, five had significant differences between P. hydropiper and P. lapathifolium. Then, we evaluated the composition of the significantly different communities between P. hydropiper and P. lapathifolium. In the P. hydropiper, the relative abundance of differential communities in the leaves was highest, of which Cercospora dominated the differential communities in the leaves and stem; in the P. lapathifolium, the relative abundance of differential community in the stem was highest, and Cladosporium dominated the differential communities in the three compartments. By constructing the interaction network of P. hydropiper and P. lapathifolium and analyzing the network nodes, we found that the core community in P. hydropiper accounted for 87.59% of the total community, dominated by Cercospora; the core community of P. lapathifolium accounted for 19.81% of the total community, dominated by Sarocladium. Of these core communities, 23 were significantly associated with active ingredient content. Therefore, we believe that the community from Cercospora significantly interferes with recruiting fungal communities in P. hydropiper and affects the accumulation of secondary metabolites in the host plant. These results provide an essential foundation for the large-scale production of P. hydropiper. They indicate that by colonizing specific fungal communities, secondary metabolic characteristics of host plants can be helped to be shaped, which is an essential means for developing new medicinal plants.